Problematika Pembelajaran Jarak Jauh pada Keluarga Petani di MI Ma’arif NU Karanggedang 2 Purbalingga - Unik Fepriyanti; Novan Ardy Wiyani (Jurnal Kependidikan, 2020)
Abstract This study aims to describe the problem of distance learning in farming families in MI Ma'arif NU Karanggedang 2 Purbalingga. This research uses qualitative research methods or often referred to as naturalistic research methods, namely research conducted in natural conditions or natural settings. For almost a year, since the Covid-19 pandemic season, learning, which was originally carried out directly and centered on schools, has now changed to a distance learning system via online or online. Now, parents of students are required to be able to be good teachers for their children at home. Not a few parents have encountered various problems related to this distance learning process. Parents' hearts are screaming, restless, restless, and even have entered a stressful stage. They are not ready to face the changes in the education system for their children in this pandemic season. Various problems in distance learning, especially in farming families, were revealed in this study. There are three problems experienced by parents of students who work as farmers, namely technology problems, skills problems, and personal problems. Keywords: farming families, problematics, distance learning, problematics. Abstrak Penelitian ini bertujuan untuk mendeskripsikan tentang problematika pembelajaran jarak jauh pada keluarga petani di MI Ma’arif NU Karanggedang 2 Purbalingga. Penelitian ini menggunakan metode penelitian kualitatif atau sering disebut sebagai metode penelitian naturalistik yaitu penelitian yang dilakukan dengan kondisi alamiah atau natural setting. Selama hampir satu tahun, sejak musim pandemi covid-19 pembelajaran yang semula dilaksanakan secara langsung dan berpusat di sekolah-sekolah, kini berganti dengan sistem pembelajaran jarak jauh via online atau daring. Kini, orang tua siswa diharuskan mampu menjadi guru yang baik untuk anak-anaknya di rumah. Tidak sedikit orang tua yang mendapatkan berbagai permasalahan terkait proses pembelajaran jarak jauh ini. Hati orang tua menjerit, resah, gelisah, bahkan sudah masuk tahap stress. Mereka belum siap menghadapi perubahan sistem pendidikan untuk anak-anaknya di musim pandemi ini. Berbagai permasalahan dalam pembelajaran jarak jauh khususnya pada keluarga petani terungkap dalam penelitian ini. Ada tiga pokok persoalan atau problematika yang dialami oleh para orang tua siswa yang berprofesi sebagai petani yaitu problematika teknologi, problematika keterampilan, dan problematika personal. Kata Kunci: keluarga petani, pembelajaran jarak jauh, problematika.